2006
DOI: 10.1111/j.1467-842x.2006.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Laplace's Boundary‐mode Approximations to Estimate Species and Shared Species Richness

Abstract: The Laplace method for approximating integrals is a useful technique in a number of research fields. This paper shows that it also has interesting applications in biological and ecological statistical inferences. When sample abundance or replicated incidence (i.e., presence or absence) records of each species are available, the expected low-order frequency counts in heterogeneous communities can be approximated by the Laplace method when the species discovery or detection probabilities are bounded from below b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 23 publications
1
31
0
5
Order By: Relevance
“…edu.tw/softwareCE.html). The bias-corrected Chao 1 estimate (Shen et al 2003;Chao 2005;Chao et al 2006) was chosen because other methods did not calculate number of species from small samples. There was a strong positive correlation between observed and estimated number of species and statistical models based on these two data sets gave similar results (see, Supplementary material for results of the stepwise regression analysis made on estimated number of species and for some cautions on the possible biases when interpreting these results).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…edu.tw/softwareCE.html). The bias-corrected Chao 1 estimate (Shen et al 2003;Chao 2005;Chao et al 2006) was chosen because other methods did not calculate number of species from small samples. There was a strong positive correlation between observed and estimated number of species and statistical models based on these two data sets gave similar results (see, Supplementary material for results of the stepwise regression analysis made on estimated number of species and for some cautions on the possible biases when interpreting these results).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For comparison, the work of Chao et al [22] is primarily concerned with asymptotic estimates for frequency counts f k of species represented by k individuals from a sample of n. In our notation, from equation (1.1), the expectation value of f 0 , for example, is given by…”
Section: Discussionmentioning
confidence: 99%
“…a for j ¼ 1, 2,. . ., S* and that the p j have 'a common marginal density g(x)' so that one has the following equation (before eqn 6 in [22] equation (A 7). In other words, the methods presented by Chao et al [22] are confined to asymptotic expansions in powers of n 21 , which we have shown in §3b to provide poorer fits to real data in comparison with equation (2.7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations